EVALUASI KINERJA BADAN PERMUSYAWARATAN DESA DALAM MELAKSANAKAN FUNGSI PENGAWASAN: (Studi Di Desa Tanomeha, Kecamatan Kaledupa Selatan, Kabupaten Wakatobi) - Nasrin Nasrin; Darmawan Wiridin; Luski Rezi (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2023)
In writing this thesis the author discusses the performance of the village consultative body in carrying out its functions and roles. The purpose of writing this journal is U To find out how the implementation of the supervisory function of BPD in Indonesia. In addition, to find out whether the implementation of the BPD's supervisory function on the performance of the Village Head in Tanomeha Village, South Kaledupa District, Wakatobi Regency has been in accordance with the Act. This research is a normative juridical legal writing using a statutory approach and a conceptual approach. The statutory approach is carried out by analyzing statutory regulations related to the supervisory function of the BPD and village government. The results showed that the village government was the village executive and the BPD was the village legislature. The Village Consultative Body (BPD) as a legislative institution and a forum that functions to establish village regulations with the village head, accommodate and channel the aspirations of the community. The existence of the BDP in Tanomeha Village has not been maximized, and the BPD still does not understand well its duties and functions as a BPD. In addition, there are several factors that hinder the implementation of the duties and functions of the BPD in Tanomeha village, such as the lack of adequate facilities, especially the secretariat, communication patterns between BPD members that are not well established, the lack of education level of BPD members where only the head of the BPD has a bachelor's degree, and busyness. higher than the members of the BPD.